Scalable parallel graph coloring algorithms - Gebremedhin, Assefaw Hadish; Manne, Fredrik (Concurrency (Chichester, England.), 2000)
Finding a good graph coloring quickly is often a crucial phase in the development of efficient, parallel algorithms for many scientific and engineering applications. In this paper we consider the problem of solving the graph coloring problem itself in parallel. We present a simple and fast parallel graph coloring heuristic that is well suited for shared memory programming and yields an almost linear speedup on the PRAM model. We also present a second heuristic that improves on the number of colors used. The heuristics have been implemented using OpenMP. Experiments conducted on an SGI Cray Origin 2000 supercomputer using very large graphs from finite element methods and eigenvalue computations validate the theoretical run‐time analysis. Copyright © 2000 John Wiley & Sons, Ltd.